The percentage of ALK-positive cells and the efficacy of first-line alectinib in advanced non-small cell lung cancer: is it a novel factor for stratification? (Turkish Oncology Group Study) - Hizal, Mutlu; Bilgin, Burak; Paksoy, Nail; Atci, Muhammed Mustafa; Kahraman, Seda; Kilickap, Saadettin; Sendur, Mehmet Ali Nahit (Springer, 2023)
Introduction Alectinib is an effective second-generation ALK tyrosine kinase inhibitor (TKI) used in the first-line treatment of patients with advanced ALK-positive NSCLC. Recent studies demonstrated that the percentage of ALK-positive tumor cells in patient groups receiving crizotinib might affect outcomes. This study aimed to investigate whether the percentage of ALK-positive cells had a predictive effect in patients with advanced NSCLC who received first-line Alectinib as ALK-TKI. Materials and methods This retrospective study included patients with advanced-stage NSCLC who received alectinib as a first-line ALK-TKI and whose percentage of ALK-positive cells was determined by FISH at 27 different centers. Patients who received any ALK-TKI before alectinib were not included in the study. Patients were separated into two groups according to the median (40%) value of the percentage of ALK-positive cells (high-positive group >= 40% and low-positive group < 40%). The primary endpoint was PFS, and the secondary endpoints were OS, ORR, and PFS of the subgroups based on different threshold values for the percentage of ALK-positive cells. Results 211 patients were enrolled (48.3% female, 51.7% male) to study. 37% (n = 78) of the patients had received chemotherapy previously. After a median of 19.4 months of follow-up, the median PFS was not reached in the high-positive group (n = 113), but it was 10.8 months in the low-positive group (n = 98) (HR 0.39; 95% CI 0.25-0.60, p < 0.001). The median OS in the high-positive group was not reached, whereas it was 22.8 months in the low-positive group (HR 0.37; 95% CI 0.22-0.63, p < 0.001). ORR was significantly higher in the high-positive group (87.2 vs. 68.5%; p = 0.002). According to the cut-off values of < 20%, 20-39%, 40-59%, and >= 60%, the median PFS was 4.5, 17.1, and 26 months, respectively, and could not be reached in the >= 60% group. Conclusion Our study demonstrated that the efficacy of alectinib varies significantly across patient subgroups with different percentages of ALK-positive cells. If these findings are prospectively validated, the percentage of ALK-positive cells may be used as a stratification factor in randomized trials comparing different ALK-TKIs.
Keywords: Alectinib; Percentage of ALK-positive cells; Break-apart; Predictive; Response